New Aspects of ZZ Transform to Fractional Operators With Mittag-Leffler Kernel - Jena, Rajarama Mohan; Chakraverty, Snehashish; Baleanu, Dumitru; Alqurashi, Maysaa M. (Frontiers in Physics, 2020)
In this paper, we discuss the relationship between the Zain Ul Abadin Zafar (ZZ) transform with Laplace and Aboodh transforms. Further, the ZZ transform is applied to the fractional derivative with the Mittag-Leffler kernel defined in both the Caputo and Riemann-Liouville sense. In order to illustrate the validity and applicability of the transform, we solve some illustrative examples.